68Ga-DOTATATE positron emission tomography/computed tomography to detect the recurrence of phosphaturic mesenhcymal tumor-induced osteomalacia - Bhalla, Manav I.; Wirtz, Kennedy M.; Fair, Eric S.; Bucklan, Daniel J. (World Journal of Nuclear Medicine, 2020)
68Ga-DOTATATE positron emission tomography/computed tomography (PET/CT) has shown superiority over111Indium-octreotide scanning for the detection of phosphaturic mesenchymal tumors (PMTs). We report a case of tumor-induced osteomalacia resulting from PMT which, although initially clinically suspected, was not localized on octreotide scintigraphy performed several years prior. Subsequent surgical excision of a presumed benign osseous lesion a few years later revealed the diagnosis on pathology. Imaging assessment using 68Ga-DOTATATE PET/CT following recent clinical suspicion for recurrence revealed an intense tracer-avid lesion at the primary tumor site. DOTATATE imaging plays an important role in localizing tumors with high somatostatin receptor expression, such as neuroendocrine tumors (pheochromocytoma, paraganglioma, and neuroblastoma), meningioma, and mesenchymal tumors, causing oncogenic osteomalacia.
Keywords: 68Ga-DOTATATE; phosphaturic mesenchymal tumor; positron emission tomography; somatostatin receptors; tumor-induced osteomalacia